2011
DOI: 10.1111/j.1526-4637.2011.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Complications from Epidural Steroid Injections

Abstract: Fluoroscopically guided epidural steroid injections are a safe and well-tolerated intervention for cervical or lumbar pain and radiculopathy. Minor complications are uncommon, and most involve increases in pain. Transforaminal injections may result in fewer minor complications than interlaminar injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 32 publications
4
94
2
1
Order By: Relevance
“…A disadvantage in using epidural anesthesia is the complications that may arise as a result of this route of administration, including postdural puncture headache 10 and increased postprocedural pain. 11 Shafiq et al 12 reported an overall complication rate of 26.6%, including motor block, dural tap, ineffective pain control, accidental catheter pullouts, and problems associated with the delivery system of the drug. In addition to the mode of anesthesia, the follow-up in our report was much longer than that of Aspegren et al Their study reported only a follow-up of 45 days after the post-MUA therapy was complete, 5 whereas ours included pain and disability scores 12 months after post-MUA therapy.…”
Section: Discussionmentioning
confidence: 98%
“…A disadvantage in using epidural anesthesia is the complications that may arise as a result of this route of administration, including postdural puncture headache 10 and increased postprocedural pain. 11 Shafiq et al 12 reported an overall complication rate of 26.6%, including motor block, dural tap, ineffective pain control, accidental catheter pullouts, and problems associated with the delivery system of the drug. In addition to the mode of anesthesia, the follow-up in our report was much longer than that of Aspegren et al Their study reported only a follow-up of 45 days after the post-MUA therapy was complete, 5 whereas ours included pain and disability scores 12 months after post-MUA therapy.…”
Section: Discussionmentioning
confidence: 98%
“…91 No major complications were identified. There were 103 minor complications, for an overall complication per injection rate of 2.4%.…”
Section: Complicationsmentioning
confidence: 98%
“…The TF injection technique involves the placement of a needle within a neuroforamen, does not require a loss-of-resistance technique, and must be performed with fluoroscopic guidance. The TF approach has several theoretical advantages over other routes of injection in that it is the most target-specific, carries a lower risk of inadvertent dural puncture, 91 and is associated with a greater incidence of ventral epidural spread, especially with placement of the needle in the anterior foramen. 92 However, TF ESIs are also associated with an increased risk profile compared with the caudal and IL approaches.…”
Section: Transforaminalmentioning
confidence: 99%
“…Paresthesias or radicular pain occur slightly more frequently with lumbar (13%) compared with cervical (7%) interlaminar ESI [65]. Flushing may occur during both interlaminar and transforaminal injections due to an IgE-mediated mechanism, with rates ranging from as low as 0.1% [67,72] to up to 11% [73], and may be prevented by prophylactic antihistamine medication. Persistent hiccups, likely due to stimulation of the afferent hiccup reflex arc involving either the phrenic, vagus or sympathetic nerves of T6-T12, typically resolve with conservative measures or chlorpromazine (Table 1) [74].…”
Section: Minor Complicationsmentioning
confidence: 99%